Two grooms on a cake : the story of America's first gay wedding - Sanders, Rob, 1958- (Little Bee Books, 2021)
Two wedding cake toppers tell the love story of the men they represent, Michael McConnell and Jake Baker, and their difficult journey to become the first married gay couple in the United States.